Educational Partnerships towards Long-Term Music Education Projects in Thailand - Chansitthichok, Nicha; Charanyananda, Anak; Pidokrajt, Narongchai (Malaysian Journal of Music, 2019)
There are many challenges in developing long-term music education projects in Thailand such as human resource development, educational policies and financial problems. This study examined the various educational partnerships and workflow plan used to sustain long-term music education projects in Thailand. Findings were based upon the roles and responsibilities of members and the understanding of the workflow plan of music educational partnerships towards the sustainability of music projects. This qualitative research consists of in-depth interviews with 20 informants which comprised music educators, school principals, and community leaders. Two long-term music education projects were discussed and compared in this article.  An expert focus discussion group was used to evaluate the validity and reliability of this research. Results showed that strong bond relationships developed in the respective state of educational partnerships to create long-term music education projects. The educational partnership comprised proactive music educators, music teachers, music supervisors, supportive parents and community leaders who worked together to provide the best practices for the students. This partnership can be sustained through various partnership programmes, and the well-being of working together. This study benefits the development of long-term music education in future partnership projects.